Talbert, Richard J.A. (2017). Roman portable sundials. The Empire in your hands. New York: Oxford University Press. ISBN: 9780190273484, 236 páginas - Alfaro, Juan Pablo (2018)
Fil: Alfaro, Juan Pablo. Pontificia Universidad Católica Argentina; Argentina